Murder Rates in New Orleans, La, 2004–2006 - VanLandingham, Mark J. (© American Journal of Public Health 2007, 2007)
Murder rates for New Orleans, La, during 2005 and 2006 were calculated with the best available population trajectories for these 2 atypical years. These calculations showed that the murder rate increased substantially during this period compared with 2004. The increase in 2005 from 2004 was 14%. The best estimate of the increase in the murder rate in 2006 compared with 2004 was 69%; the large increase in 2006 began during the second quarter of that year.